Multi-target neuroprotective effects of herbal medicines for Alzheimer's disease. (23rd May 2022) - Fernandes, Filipe; Barroso, M. Fátima; De Simone, Angela; Emriková, Eliška; Dias-Teixeira, Mónica; Pereira, José Paulo; Chlebek, Jakub; Fernandes, Virgínia Cruz; Rodrigues, Francisca; Andrisano, Vincenza; Delerue-Matos, Cristina; Grosso, Clara
Abstract: Ethnopharmacological relevance: Alzheimer's disease is the most common form of dementia, but its treatment options remain few and ineffective. To find new therapeutic strategies, natural products have gained interest due to their neuroprotective potential, being able to target different pathological hallmarks associated with this disorder. Several plant species are traditionally used due to their empirical neuroprotective effects and it is worth to explore their mechanism of action. Aim of the study: This study intended to explore the neuroprotective potential of seven traditional medicinal plants, namely Scutellaria baicalensis, Ginkgo biloba, Hypericum perforatum, Curcuma longa, Lavandula angustifolia, Trigonella foenum-graecum and Rosmarinus officinalis . The safety assessment with reference to pesticides residues was also aimed. Materials and methods: Decoctions prepared from these species were chemically characterized by HPLC-DAD and screened for their ability to scavenge four different free radicals (DPPH, ABTS +, O2 ‒ and NO) and to inhibit enzymes related to neurodegeneration (cholinesterases and glycogen synthase kinase-3β). Cell viability through MTT assay was also evaluated in two different brain cell lines, namely non-tumorigenic D3 human brain endothelial cells (hCMEC/D3) and NSC-34 motor neurons. Furthermore, and using GC, 21 pesticides residues were screened. Results: Regarding chemical composition, chromatographic analysis revealed the presence of several flavonoids, phenolic acids, curcuminoids, phenolic diterpenoids, one alkaloid and one naphthodianthrone in the seven decoctions. All extracts were able to scavenge free radicals and were moderate glycogen synthase kinase-3β inhibitors; however, they displayed weak to moderate acetylcholinesterase and butyrylcholinesterase inhibition. G. biloba and L. angustifolia decoctions were the less cytotoxic to hCMEC/D3 and NSC-34 cell lines. No pesticides residues were detected. Conclusions: The results extend the knowledge on the potential use of plant extracts to combat multifactorial disorders, giving new insights into therapeutic avenues for Alzheimer's disease. Graphical abstract: Image 1